2019
DOI: 10.1111/psyp.13505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative conditioning affects the subsequent acquisition of differential fear conditioning as indexed by electrodermal responding and stimulus evaluations

Abstract: It is currently unclear whether the acquisition of negative stimulus valence in evaluative and fear conditioning paradigms is interrelated or independent. The present study used a transfer paradigm to address this question. Three groups of participants were trained in a picture‐picture evaluative conditioning paradigm before completing acquisition of differential fear conditioning using graphical shapes as conditional stimuli (CSs). In group congruent, the shape used as CS+ (paired with the US during fear cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This is the most commonly used subjective measure in human conditioning paradigms (Lonsdorf et al, 2017). However, Lipp et al (2020) found that evaluative and conditioning are not independent, and it is necessary to incorporate associative and evaluative learning measures (Constantinou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is the most commonly used subjective measure in human conditioning paradigms (Lonsdorf et al, 2017). However, Lipp et al (2020) found that evaluative and conditioning are not independent, and it is necessary to incorporate associative and evaluative learning measures (Constantinou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%